Histological analysis of state of tissues in internal organs of black-backed shad Alosa kessleri kessleri - Maria P. Grushko; Nadezhda N. Fedorova; Alina A. Aitimova (Известия ТИНРО)
Internal organs of black-backed shad are examined by histological analysis. Wide range of pathologies is found, which are supposedly caused by chronic environmental pollution. The pathologies of tissue and cellular levels have common features but various symptoms, as edema, hemorrhage, necrosis, inflammation, connective tissue proliferation, proliferative changes in the epithelium. The gills, liver; kidney, and intestines are the most sensitive to negative impacts of environments.